The Impact of Digitalization on Economic Growth in Indonesia: An Analysis Spline Approach - Syaiful; Samin Saputra; Yolanda Yolanda (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Digitalization is currently developing very rapidly, and various studies have shown that it contributes to increased economic growth in various countries. In Indonesia, the development of digitalization is a crucial factor in driving economic growth between provinces with varying levels of technology adoption. Therefore, this study aims to explore the influence of digitalization on economic growth in Indonesia and identify the contribution of each digitalization indicator to economic growth in each province based on digitalization clusters. This study uses one dependent variable, namely economic growth, which is proxied by GRDP per capita, and five independent variables as digitalization indicators: digital access, digital use, digital capability, digital finance, and digital inequality. The analysis method used is a spline approach to capture differences in influence between provincial clusters. The research results show that the digital capability indicator contributed the most to the increase in GRDP per capita in provinces with the “Very High” cluster, followed by Digital Finance. Thus, digitalization has been shown to significantly influence economic growth in Indonesia. Improving infrastructure and adopting digital technologies, as well as reducing the digital divide, are crucial for driving inclusive and sustainable economic growth across all provinces.